Michel Henry's Transcendental Asexuality - Justin Pearl (Aisthema: International Journal, 2022)
Since his earliest speculations in The Essence of Manifestation (1963), Michel Henry’s radical phenomenology has highlighted the importance of the flesh and eros as central figures of the duality of appearance. Yet, in his prioritization of the affective flesh Henry has systematically bracketed “concrete sexual determinations” from the immanence of the flesh. That is to say, for Henry, the fundamental human person manifests in the mode of transcendental a-sexuality. This bracketing of sexual determinations from the affective flesh opens Henry’s analysis of incarnation and eros to the subtle insinuation of a determinatively masculine “universal subject,” a regression to stereotyped notions of femininity, and deeply troubling accounts of queer sexuality. In the present investigation, I aim to trace Henry’s thought from his account of the flesh into his analysis of the erotic encounter and, through an engagement with the French feminist tradition contemporary to his own work, expose the limits of his analysis of the incarnation and eros. Ultimately, I aim to suggest not that Henry’s radical phenomenology should be abandoned or condemned, but rather that a recuperation of a liberative phenomenology of sexuality requires a more consistent employ of Henry’s radical phenomenological method.